2011
DOI: 10.1007/s00266-011-9845-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Longevity and Results of Mastopexy and Breast Reduction Procedures: Reconstructing an Internal Breast Support System with Biocompatible Mesh to Replace the Supporting Function of the Ligamentous Suspension

Abstract: BackgroundThe reasons for recurrent ptosis in mastopexy and breast reduction procedures are twofold. First, available surgical techniques do not reconstruct the normal breast anatomy responsible for maintaining breast shape. Second, in many instances the techniques rely on atrophied tissue to provide long-term support. The discovery in 1997 of the ligamentous suspension (the supporting system of the breast) gave rise to the concept that reconstruction of this anatomical structure was needed to ensure a sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…As with any cosmetic elective procedure, the costs and risk to benefit ratio must be carefully weighed in such cases. The current surgical use of PADM is similar to that described in a recent report of the successful use of ADM as an internal bra for patients with ptosis undergoing primary mastopexy, either alone or in combination with breast reduction [8]. The current findings supplement those of this earlier study and suggest that PADM also may be used in similar patients who wish to undergo breast implant surgery.…”
Section: Discussionsupporting
confidence: 81%
“…As with any cosmetic elective procedure, the costs and risk to benefit ratio must be carefully weighed in such cases. The current surgical use of PADM is similar to that described in a recent report of the successful use of ADM as an internal bra for patients with ptosis undergoing primary mastopexy, either alone or in combination with breast reduction [8]. The current findings supplement those of this earlier study and suggest that PADM also may be used in similar patients who wish to undergo breast implant surgery.…”
Section: Discussionsupporting
confidence: 81%
“…Statistical analysis showed that there is a high statistical significance difference between three measurements of SN distance. The mean values and standard deviation of the N-IMF distances are shown in Tables (3,4). Statistical analysis showed that there is a high statistical significance difference between three measures of N-IMF distance.…”
Section: Resultsmentioning
confidence: 99%
“…Breast ptosis results from weakening and lengthening of the supporting structures of the breast [4]. Therefore, correction of ptosis and restoring youthful breasts remains a challenge in breast aesthetic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23]31 Therefore, a one-stage procedure has been proposed with extension of the submuscular pocket by release of the inferior pectoralis major attachments and its completion by a foreign material such as biological matrices or synthetic mesh. [34][35][36] This surgical experience has demonstrated good tolerance of this foreign material. [34][35][36] This surgical experience has demonstrated good tolerance of this foreign material.…”
Section: Discussionmentioning
confidence: 99%